The Influence of Sales Growth, Capital Structure and Company Size on Company Value : Empirical Study of Food and Beverage Sub-Sector Manufacturing Companies Registered on BEI 2016-2020 - Haryati, Fitri; Sugiharti Sugiharti; Firdaus, Firdaus; Purwanto, Dedik; Wahyu Alfiana, Elsa; Alif Rizky Bunganaen, Naufal; Dwi Yulian, Adinda (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2024)
The current economic development follows the era of globalization which has a positive impact and influence on existing companies, especially in Indonesia, the food and beverage industry has an important role in people's lives as providers of primary needs.The analytical method used in this research is descriptive statistical analysis, classical assumption test, multiple linear regression analysis, and hypothesis testing. The sample taken in this study used a purposive sampling technique. In line with that, there are 35 company data in the annual report as a sample in this study.Based on the results of hypothesis testing conducted in this study, it can be concluded that partially each independent variable Sales Growth has no effect on firm value, capital structure has no effect on firm value, and firm size has a positive effect on firm value. Similarly, the results of simultaneous testing of all independent variables Sales Growth, Capital Structure and Firm Size have a positive effect on Firm Value.